The Incidence of Vaginal Deliveries in Obese Mothers at Prof Dr. I.G.N.G Ngoerah Hospital In 2022 - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Ni Wayan Dewi Purwanti; Made Diah Vendita Sakuntari; Ni Putu Nining Gianni; Ni Luh Made Diah Mas Cahyani Putri; Ni Luh Md Dwi Laxmi Satriani; Firsta Sesarina Mintariani; Ketut Widyani Astuti (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2023)
Introduction: One of the risk factors seen most frequently in obstetric practice is maternal obesity. Women who were overweight or obese made up more than half of all female fatalities due to direct or indirect causes. Obesity increases the chance that the mother will experience obstetric problems during pregnancy, labour, and delivery, making fetal assessment more technically difficult. Methods: This study uses quantitative descriptive univariate analysis. The type of data is secondary data taken from the birth register. This study examines women who gave birth in 2022 and were identified as belonging to the obesity category by Prof. Dr. I. G. N. G. Ngoerah Denpasar General Hospital. Results: At Prof.dr.I.G.N.G Ngoerah Denpasar General Hospital, 21 obese pregnant women will give birth throughout 2022. Of the 21 people, 81% give birth by emergency C-section, 4,8% by elective C-section, and 14,2% give birth vaginally. Obese pregnant women have a higher risk of needing a cesarean section. Patients with obese class III had a significantly higher risk of infant morbidity than those with a normal BMI, according to their findings. Conclusions: Obese pregnant women are at increased risk of having a cesarean section. Therefore, health workers must provide knowledge to pre-pregnant or pre-marital women to maintain their BMI so they do not become obese during pregnancy. Thus, morbidity and mortality rates can also be reduced.